FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ASMA DI WILAYAH PERKOTAAN DAN PEDESAAN INDONESIA: ANALISIS DATA SURVEI KESEHATAN INDONESIA (SKI) 2023 - Monica Evi Fania Girsang; Muhammad Syukri; Rd Halim; Adelina Fitri; Herman Herman (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2026)
Asthma is a chronic respiratory disease characterized by shortness of breath due to inflammation and narrowing of the airways. Differences in prevalence between urban and rural areas indicate differences in risk factors influenced by geographic, environmental, and social contexts. This study aims to analyze factors associated with asthma incidence in the population aged ≥15 years in Indonesia based on differences in residential areas (urban and rural). This study is a secondary data analysis using the Indonesian Health Survey (SKI). The sample of this study was 638,178 respondents aged ≥15 years. Data analysis consisted of univariate descriptive statistics, bivariate and multivariate logistic regression to identify independent predictors. The prevalence of asthma was 1.8%, with a higher proportion in urban areas (2.1%) than in rural areas (1.5%). In multivariate analysis, Factors related to the occurrence of asthma in urban areas are age (POR=1,15; 95%CI: 1,05–1,26), gender (POR=1,36; 95% CI: 1,26-1,48), obesity (POR=1,27; 95%CI: 1,16–1,40), central obesity (POR=1,34; 95% CI: 1,23-1,45), ISPA (POR = 4,15; 95% CI: 3,48–4,94), TB (POR = 3,55; 95% CI: 2,35–5,35) And in rural areas is age (POR=1,42; 95%CI: 1,24–1,63), central obesity(POR=1,37; 95% CI: 1,23–1,53), physical activity (POR = 1,37; 95% CI: 1,23–1,53), ISPA (POR = 4,06; 95%CI: 3,17–5,20), TB (POR = 6,78; 95% CI: 4,62–9,97).The dominant factor in urban areas is a history of acute respiratory infections (ARI) (p-value= 0.000; AdjPOR=3.95; 95%CI 3.30-4.71), while in rural areas is a history of tuberculosis (TB) (p-value= AdjPOR=4.81; 95%CI 2.18-7.27). Conclusion: There are differences in the dominant determinants of asthma incidence between urban and rural areas in Indonesia. A history of ARI is the main factor in urban areas, while a history of tuberculosis is more influential in rural areas. These findings emphasize the importance of an asthma control policy approach that is based on geographic context and integrated with respiratory tract infection control programs.